(untitled) (Cambridge, 1989)
The author shows how similarities and differences between languages can influence grammar, vocabulary, and pronunciation acquisition.
Tiếp thu ngôn ngữ thứ hai tiếng Anh
Keywords: second language acquisition,applied linguistics